1989
DOI: 10.1002/1098-108x(198903)8:2<131::aid-eat2260080202>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Defense styles and parental bonding in eating-disordered women

Abstract: Fifty-eight women with anorexia or bulimia nervosa were compared with 24 normal women on measures of defense style and parental bonding. Results indicated that all eating-disorder subtypes exhibit more primitive defenses and fewer mature ones than controls. Eating-disorder patients uniformly recalled less paternal empathy than controls. Thus, difficulties involving object representations of fathers may be a theme common to eating disorders. No major differences were identified among eating-disorder subtypes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
43
4

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 27 publications
7
43
4
Order By: Relevance
“…In a nonreferred cohort of 1,193 adolescents in Norway (Lavik, Clausen, & Pedersen, 1991), total EAT score was significantly correlated with perceived overprotection by the mother. However, these results contrast with Palmer, Oppenheimer, and Marshall (1988) who found no consistent pattern of parental practices in anorexic and bulimic patients or with Steiger, van der Feen, Goldstein, and Leichner (1989) who found absence of paternal care in such patients. Such a discrepancy may be attributable to the qualitative difference between a patient population and a nonclinical one, pointing to the discontinuity between them; or, it may represent a Berkson bias on the part of the studies with patient populations that might have arrived at false conclusions because the combination of the disease and the risk factors were underrepresented in those presenting to the hospitals and seeking treatment.…”
Section: Discussioncontrasting
confidence: 86%
“…In a nonreferred cohort of 1,193 adolescents in Norway (Lavik, Clausen, & Pedersen, 1991), total EAT score was significantly correlated with perceived overprotection by the mother. However, these results contrast with Palmer, Oppenheimer, and Marshall (1988) who found no consistent pattern of parental practices in anorexic and bulimic patients or with Steiger, van der Feen, Goldstein, and Leichner (1989) who found absence of paternal care in such patients. Such a discrepancy may be attributable to the qualitative difference between a patient population and a nonclinical one, pointing to the discontinuity between them; or, it may represent a Berkson bias on the part of the studies with patient populations that might have arrived at false conclusions because the combination of the disease and the risk factors were underrepresented in those presenting to the hospitals and seeking treatment.…”
Section: Discussioncontrasting
confidence: 86%
“…Other studies have shown evidence of both specificity ) and lack of specificity ) of the DSQ with clinical diagnoses. Several studies have looked at the DSQ in clinical samples of women with eating disorders (Steiger, Goldstein, Mongrain, & Van der Feen, 1990;Steiger, Van der Feen, Goldstein, & Leichner, 1989;Steiner, 1990). These studies demonstrate substantially greater defensive pathology in eating disorder groups in comparison to controls without consistent results regarding differences among the various eating disorders.…”
mentioning
confidence: 99%
“…These studies demonstrate substantially greater defensive pathology in eating disorder groups in comparison to controls without consistent results regarding differences among the various eating disorders. However, two of these reports appeared to have studied substantially the same individuals (Steiger et al, 1989(Steiger et al, , 1990. Additional limitations of these studies include the use of an early version of the DSQ (Bond et al, 1983) and its problematic scoring algorithm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, there has been a considerable amount of empirical research involving the use of parent-child relationship dynamics or attachment theory as conceptual frameworks for understanding the etiology of disordered eating. In terms of parent-child relationships, women with disordered eating reported their fathers as emotionally unavailable and highly critical of them (Cole-Detke & Kobak, 1996), the lack of parental care or empathy (Steiger, Van der Feen, Goldstein, & Leichner, 1989), or high parental hostility (Becker, Bell, & Billington, 1987). Also, M. E. Kenny and Hart (1992) reported that college students with secure parental attachment reported lower levels of weight and dieting preoccupation, bulimic behavior, and feelings of inadequacy compared to women with eating disorders.…”
Section: Attachment and Disordered Eating Attitudesmentioning
confidence: 99%